Sungai Bengawan Solo: Jalur Perdagangan di Jawa Era Pakubuwono X - Martastia Nugraheni; Hilyatil Zilfa Najmi (PT Inovasi Penelitian Terpadu, 2025)
During the reign of Pakubuwono X (1893–1939), the Bengawan Solo River was an important trade route connecting the interior with the north coast of Java. This study investigates the strategic role of this river in the trade and transportation activities of Javanese society and the impact of colonial rule on trade dynamics along its course. This study finds that the Bengawan Solo had high economic value because it delivered agricultural commodities, forest products, and local crafts to major ports such as Gresik. This is achieved through the application of a qualitative approach and analysis of primary and secondary sources. In addition, it is found that the river's function as an important route for the transportation of goods was strengthened by the development of river infrastructure such as the Demangan sluice gate. The river remained the center of regional trade during that time, although land transportation such as railways began to develop. Local and colonial economic networks were strengthened by trade through river ports, land and air transportation, and the role of cities such as Surakarta and Ngawi. To understand how Javanese trade was in the early 20th century, revitalizing local historical narratives is essential.